Agreement between different eGFR equations in diagnosing contrast-induced acute kidney injury in patients undergoing elective coronary or peripheral angiography - Somkereki Cristina; Nicoară Tunde Renata; Oprica Mădălina; Demian Liliana; Scridon Alina (Romanian Journal of Laboratory Medicine, 2024)
In the present study, we aimed to compare CKD-EPI, MDRD, CKD-EPI creatinine-cystatin C equations and serum cystatin C and NGAL levels changes in assessing the occurrence of contrast-induced acute kidney injury (CI-AKI) in patients undergoing coronary and peripheral angiography and to evaluate the agreement between the CKD-EPI formula and the other parameters.